Tres circuitos migratorios Puebla-Estados Unidos: una lectura comparativa - Maria Eugenia D’Aubeterre Buznego (Centre de Recherches sur les Mondes Américains, 2007)
Nowadays, Mexican migration to the United States is characterized by its socio-demographic heterogeneity and multiethnic character; moreover, men and women join the migration circuits on the basis of their specific gender condition.  As the profile of these flows and the pattern of displacement have changed, new analytical perspectives and methodological strategies have been adopted. In a context of changing scenery and diversification of migratory origins and destinations, central Mexican states have assumed an important presence from the end of the decade of the nineteen seventies as this region turned into a zone of emerging international migration. In this essay we propose to compare the international migratory dynamic in three circuits which are connected with an equal number of micro-regions: on the one hand the Center, South and the Mixteca regions in Puebla; on the other, East Los Angeles in California, New York City and coastal localities of the state of New Jersey.  We also analyze the differences in the insertion of male and female migrant workers into informal commerce and services.